ANALISA PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DAN PERBANKAN KONVENSIONAL DI INDONESIA PERIODE TAHUN 2011-2013 - Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to identify and analyze comparative financial performance of Islamic bankingand conventional banking in Indonesia in terms of the level of profitability, capital, efficiency, liquidityand asset qualityThe study population was the entire Islamic banks and conventional banks operating in Indonesia.Sampling using purposive sampling technique, in which a sample is used if it meets the criteria; stilloperates on the study time period, the data available financial statements, and has total assets ofbetween Rp 1 trillion to Rp 50 trillion as of 31 December 2013. Islamic commercial bank that is used asthe sample amounted to 8 banks, and conventional commercial banks amounted to 33 banks. The datais processed using different test average (independent sample t-test).The results showed that the bank profitability ratios ROE seen from there are significant differencesbetween Islamic banking and conventional banking. Seen from the CAR capital there are significantdifferences between Islamic banking and conventional banking, bank liquidity seen from the LDR orFDR there are also significant differences between Islamic banking and conventional banking. Whilethe efficiency and quality of the assets which each seen from the ratio of ROA and NPL / NPF there areno significant differences between Islamic banking and conventional banking.Keywords: Financial Performance, Profitability, Capitalization, Efficiency, Liquidity, AssetsQuality, Islamic Bank, Bank Conventional.